Technical Guidance for Raising Gourami Fish in the Round Pond System to Pokdakan Karya Maju, Karya Tani Village - Akhmad Murjani; Siswanto Siswanto; Akhmad Nizar (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
The purpose of this service activity is to increase the knowledge and skills of the Karya Maju Fish Farmers Group (Pokdakan) in Karya Tani Village, Barambai District, Barito Kuala Regency regarding the enlargement of gourami in the round pond system. The approach method used is the delivery of material through socialization, hands-on practice in installing circular pools, question and answer which is then carried out by evaluating the knowledge and skills of the target audience. The results showed that there was an increase in knowledge and skills where previously the number of target audience who have no knowledge and skills about growing gouramy in the round pond system 80%, then decreased to 0%. In practices, the gouramy grew 92% for 30 days of rearing with a mortality rate only 8% and the calculation results were declared economically viable.